Enhancing wikis with visualization tools to support groups production function and to maintain task and social awareness - AL-Smadi, M.; Hoefler, M.; Guetl, Christian (International Association of Online Engineering, 2011)
The emergence of web 2.0 and the influence of Information and Communication Technology (ICT) have fostered e-learning to be more interactive, challenging, and situated. As a result, learners have gained more empowerment through collaborative learning activities and self-directed learning. Moreover they are provided with computer-based social environments to discuss and collaborate by which they are encouraged to reflect on others’ contributions in a way that may facilitate collaborative knowledge construction. The use of wikis in education as an example of these social environment lacks students’ motivators namely assessment activities and group work support. This paper proposes an enhanced wiki system for collaborative writing assignments. Moreover, it discusses how a wiki can be enhanced with visualization tools to maintain task and social awareness and support group production function. Nevertheless, it shows how integrated self and peer-assessment activities may increase engagement and maintain group well-being.